The South African labour market, 1995–2015. Issue 5 (2nd September 2016) - Festus, Lyle; Kasongo, Atoko; Moses, Mariana; Yu, Derek
ABSTRACT: This study investigates the changes in the South African labour market in the post-apartheid period. While unemployment increased over the 1995–2015 period, employment also increased. Nonetheless, the extent of employment increase is not rapid enough to absorb all net entrants into the labour force, resulting in increasing unemployment, or an employment absorption rate of 65.3%. Unemployment is concentrated in specific demographically and geographically defined groups, most notably Africans, the lowly educated and those aged below 30 years, residing in rural areas in Gauteng. Finally, four worrying findings are observed: youth jobseekers aged below 30 years struggle to find their first job; chronic unemployment is more serious for the relatively older jobseekers (aged 45 years or above) with past work experience; employees working for small, medium and micro enterprises still stagnate at approximately 3.5 million; and jobseekers from the older age cohorts are less likely to actively seek work by enquiring at workplaces and answering job advertisements.